2023
DOI: 10.1021/acssuschemeng.2c06077
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Transition Facilitated by Bitcoin

Abstract: Reduction of greenhouse gas emissions has been a top priority for activists, scientists, and policy makers across the globe, and it is one of the main drivers for the transition to renewable energy generation. Bitcoin is a decentralized global transaction network of an eponymous digital currency. It has been praised for its openness, decentralization, and censorship resistance, as well as criticized for its inefficiency, criminal use, and enormous electricity consumption. We discuss the challenges in the renew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Although the findings of this study indicate that bitcoin mining presents innovative opportunities in utilizing surplus renewable energy from planned renewable installations and facilitating energy transition, it is also imperative to acknowledge the broader concerns associated with it. Bitcoin mining continues to be highly energy-intensive due to the adopted consensus algorithm . The annual energy consumption of bitcoin mining stands at 115 TW h, equivalent to the power consumption of The Netherlands .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the findings of this study indicate that bitcoin mining presents innovative opportunities in utilizing surplus renewable energy from planned renewable installations and facilitating energy transition, it is also imperative to acknowledge the broader concerns associated with it. Bitcoin mining continues to be highly energy-intensive due to the adopted consensus algorithm . The annual energy consumption of bitcoin mining stands at 115 TW h, equivalent to the power consumption of The Netherlands .…”
Section: Resultsmentioning
confidence: 99%
“…Bitcoin mining continues to be highly energy-intensive due to the adopted consensus algorithm. 57 The annual energy consumption of bitcoin mining stands at 115 TW h, equivalent to the power consumption of The Netherlands. 58 Based on this energy consumption, previous studies have pointed out the significant climate impact stemming from bitcoin due to the power supply from nonrenewable sources.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They reported that renewable energy applications for cryptocurrency mining could reduce environmental impacts and network problems. Velický 25 addressed the obstacles associated with the shift to renewable energy, examined the characteristics of the Bitcoin network, and explored the involvement of Bitcoin mining operations in the global production and consumption of energy. Vega‐Marcos et al 26 proposed the development of a wind power plant to generate energy for Bitcoin mining in Spain.…”
Section: Literature Surveymentioning
confidence: 99%
“…With the widespread implementation of sustainable green power generation technologies, such as photovoltaic and wind power, the imminent future holds promise for significant alleviation of the energy crisis and environmental concerns in human society. Nevertheless, the spatial and temporal constraints inherent in these emerging energy technologies pose substantial obstacles to the efficient utilization of the generated power. , Positioned as a green, zero-carbon emission, and well-established energy conversion and storage technology, alkaline electrocatalytic water splitting for hydrogen production stands out as a solution to address the spatial and temporal disparities in new energy power distribution. It is undeniable that the high energy consumption due to the high overpotential of this technology greatly reduces the economy of this technology. Hence, the imperative to cultivate a stable, efficient, and cost-effective alkaline hydrogen evolution reaction (HER) catalyst becomes paramount in mitigating the energy demands of this technology.…”
Section: Introductionmentioning
confidence: 99%